PUBLIC PERCEPTION OF RENEWABLE ENERGY IN INDONESIA: IMPLICATION FOR COMMUNICATION STRATEGY - Mila Viendyasari; Mohammad Syukri; Erkarta Yandri; Devie Rahmawati (Jurnal Ilmiah MEA (Manajemen, Ekonomi, & Akuntansi), 2022)
In this study, the public's perception of renewable energy in Indonesia is examined, along with its communication implications. A mix method was employed in this study, which is a research strategy that blends qualitative and quantitative research. The object in this research is the Indonesian Society. From questionnaire that was distributed through the random selection, research result revealed quite different levels of perception about renewable energy concepts. To be most effective, communications strategy should be designed to answer the questions that each individual has, building upon the level of knowledge as one of perception aspect that already exists.